Local SAR compression with overestimation control to reduce maximum relative SAR overestimation and improve multi-channel RF array performance - Orzada, Stephan; Fiedler, Thomas M.; Bitz, Andreas K.; Ladd, Mark E.; Quick, Harald H. (Magnetic resonance materials in physics, biology and medicine, 2021)
In local SAR compression algorithms, the overestimation is generally not linearly dependent on actual local SAR. This can lead to large relative overestimation at low actual SAR values, unnecessarily constraining transmit array performance.
Online publiziert: 22. September 2020
Gesehen am 11.09.2025